Revival of the epic film & the Malaysian audience / Wan Aida Wan Yahaya - Wan Yahaya, Wan Aida (UPENA, 2006)
The turn of the new century has seen a massive turn in the film industry. Films are evolving with various up to date technology, and old films are being given a new breathe due to the surge in digital effects. Films.such as STAR WARS and BATMAN have returned with a vengeance as a result of all this technology. However, not only are old films brought back to life, but the global film industry has witnessed the return of the epic film. In Hollywood with epic films such as TROY and KING ARTHUR, in Thailand with the presentation of SURIYOTHAI (2001), in Indonesia with TJOET NJA DHIEN (1988) and without leaving out our own PUTERI GUNUNG LEDANG (2004), after a 16 year absence of the Malaysian epic genre. With the above in mind, the purpose of this study is to identify the possibility and the potential of future Malay epics being produced and well received by the Malaysian audience.